Aerobiology and Its Role in the Transmission of Infectious Diseases. (13th January 2013) - Fernstrom, Aaron; Goldblatt, Michael
Abstract : Aerobiology plays a fundamental role in the transmission of infectious diseases. As infectious disease and infection control practitioners continue employing contemporary techniques (e.g., computational fluid dynamics to study particle flow, polymerase chain reaction methodologies to quantify particle concentrations in various settings, and epidemiology to track the spread of disease), the central variables affecting the airborne transmission of pathogens are becoming better known. This paper reviews many of these aerobiological variables (e.g., particle size, particle type, the duration that particles can remain airborne, the distance that particles can travel, and meteorological and environmental factors), as well as the common origins of these infectious particles. We then review several real-world settings with known difficulties controlling the airborne transmission of infectious particles (e.g., office buildings, healthcare facilities, and commercial airplanes), while detailing the respective measures each of these industries is undertaking in its effort to ameliorate the transmission of airborne infectious diseases.